(untitled) (Tanzania Medical Journal, 2019)
Background Pancytopenia is the simultaneous presence of anaemia, leucopenia and thrombocytopenia. The aetiological spectrum of pancytopenia is wide and variable. We aimed to determine the common causes of pancytopenia by analyzing bone marrow aspiration records of adult patients seen at Muhimbili National Hospital, a tertiary care centre. Methods This was a retrospective descriptive cross-sectional study of all adult patients who presented with pancytopenia for a period of one year from January 2013 to December 2013. All patients with pancytopenia, i.e. Hb < 10 g/dl, WBC < 4 x 109/l and platelet count < 150 x 109/l; aged ? 18 years; and of both sexes were included in the study. The data obtained were entered on excel sheets, cleaned and analyzed for averages and ranges for numerical data. Categorical data were summarized by averages of frequencies and proportion. Results A total number of 216 adult patients had bone marrow examination in one year. A full blood picture was retrieved in 153 patients and among these, 26.8% (n = 41) had pancytopenia. The common causes of pancytopenia were aplastic anaemia (48.8%); haematological malignancies (29.3%); and nutritional anaemia (17.0%). Acute myeloid leukaemia was the commonest malignancy comprising 50% of all haematological neoplasms and iron deficiency occurred in 71.4% of nutritionally anaemic patients. Conclusion Aplastic anaemia was the most common aetiological factor followed by haematological malignancies among adult patients presenting with pancytopenia at Muhimbili National Hospital. The high frequency of iron deficiency anaemia with pancytopenia was unusual. Key words: pancytopenia, aetiology, bone marrow, adult patients